PENERAPAN METODE PEMBELAJARAN DAHSYAT “POWER TEACHING” - I Wayan Suwirya; I Nengah Astawa (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2019)
This article will discuss the Power Teaching Learning method which is more recently known as the Whole Brain Teaching method, which has the same concept as Brain Based Teaching. Power Teaching, in Indonesian can be said